Оптимізація кількості експериментальних даних у методі обчислення коефіцієнтів Фур’є за допомогою проекцій - Литвин, О. М.; Литвин, О. Г. (ПУЕТ, 2017)
Досліджується метод розв’язання задачі реконструкції зображень на основі використання скінченних сум Фур’є, запропонований автором Литвин О. М., в якому коефіцієнти Фур’є обчислюються за допомогою проекцій, що надходять з комп’ютерного томографа. Отримано співвідношення між порядком сум Фур’є, кількістю проекцій та точністю відновлення функції. Optimizing the number of experimental data in the method of calculating Fourier coefficients using projections.We study the method of solving the problem of image reconstruction based on the use of finite Fourier sums proposed by the author O.M. Litvin, where the Fourier coefficients are calculated using projections coming from the computer tomograph. Correlations between order Fourier sums, the number of projections and accurate restoration of function are given.
Keywords: реконструкція; сума Фур'є; reconstruction; image; sum Fourier